Spontaneous Common Bile Duct Perforation in Adult: A Case Report and Review - Awad, Ali J. (Journal of the Faculty of Medicine Baghdad, 2010)
Case Report: Common bile duct perforation has been reported in adults after invasive procedures, spontaneous common bile duct perforation is a rare entity as a cute abdomen in adults. A few cases due to choledocholithiasis have been reported as a cause of spontaneous perforation. We report an adult patient who presented with acute abdomen after spontaneous common bile duct perforation due to unknown etiology who was treated successfully.